2019
DOI: 10.1002/jmv.25634
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of human bocavirus infection in hospitalized children with acute gastroenteritis in South Africa, 2009‐2015

Abstract: Human bocavirus (HBoV) is known to be associated with a variety of clinical manifestation including acute gastroenteritis (AGE). Despite their global prevalence, no data is available on the epidemiology of HBoV associated with AGE in South Africa (SA). Between April 2009 and April 2015, 3765 stool specimens were collected from children less than 5 years of age hospitalized with diarrhea. Specimens were screened for selected enteric viruses by enzyme immunoassay and quantitative polymerase chain reaction, bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 38 publications
(65 reference statements)
6
17
0
1
Order By: Relevance
“…This was also the case in several other recent studies [6,34,36,37], which makes the role of HBoV4 genotype unclear. The predominance of HBoV1 and HBoV3 in children with AGE in this study is similar to a previous report in SA, which also observed a high prevalence of HBoV1 and HBoV3 [10]. However, the study only investigated HBoV in hospitalized children with AGE from an urban area, compared to this study which investigated both hospitalized and outpatients.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This was also the case in several other recent studies [6,34,36,37], which makes the role of HBoV4 genotype unclear. The predominance of HBoV1 and HBoV3 in children with AGE in this study is similar to a previous report in SA, which also observed a high prevalence of HBoV1 and HBoV3 [10]. However, the study only investigated HBoV in hospitalized children with AGE from an urban area, compared to this study which investigated both hospitalized and outpatients.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have reported human bocavirus in children with respiratory tract infections and AGE in South Africa [7][8][9][10]. However, no data are available on the prevalence of HBoV and other enteric pathogens in children with AGE from rural communities, suggesting that cases from these rural areas are most likely to be underinvestigated and under-reported [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been described that HBoV most affected age group are children up to 24-months-old [17,19,37,42]. A large study performed in South Africa between 2009 and 2015 with 3765 stool specimens collected from hospitalized children for AGE demonstrated that the majority (92%) of HBoV-positive cases were children <2 years old [20]. Furthermore, the lower rates of HBoV infection among children aged <6 months found in our study and reported elsewhere are likely due to early protection by the maternal antibodies [43][44][45], and also because usually after six-months-old, children are more exposed to viral infections within childcare centers.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, based on the genomic analysis of the two major structural proteins (VP1-2), HBoV is divided into four species or genotypes (HBoV-1 to 4) [12]. HBoV genotypes are globally distributed, and have been single or co-detected in AGE cases, with incidence varying from 0.5 to 25%, especially in children younger than two years old [10,16,[19][20][21].…”
Section: Of 14mentioning
confidence: 99%